JavaScript: Designing a Language in 10 Days. - Severance, Charles (Computer (00189162), 2012)
The evolution and use of JavaScript, a language developed in 10 days back in 1995, is really just getting started. The featured Web extra is a video interview with Mozilla's Chief Technology Officer (and JavaScript's creator), Brendan Eich.